The Expectations and Motivation Regarding Future Income and graduation of the Students of the University of Debrecen, Faculty of Engineering - Csüllög, Mihály (International Journal of Engineering and Management Sciences, 2016)
My research conducted among undergraduate students of the Faculty of Engineering of the University of Debrecen examined the students’ incentive and income expectation broken down by their gender and by their ducation level. At the same time, it aimed to measure the impact factors influencing their motivation to get the degree and their ideas regarding the payment.